Methodological standards and functional correlates of depth in vivo electrophysiological recordings in control rodents. A TASK1‐WG3 report of the AES/ILAE Translational Task Force of the ILAE. (6th November 2017) - Hernan, Amanda E.; Schevon, Catherine A.; Worrell, Gregory A.; Galanopoulou, Aristea S.; Kahane, Philippe; de Curtis, Marco; Ikeda, Akio; Quilichini, Pascale; Williamson, Adam; Garcia‐Cairasco, Norberto; Scott, Rod C.; Timofeev, Igor
Summary: This paper is a result of work of the AES/ILAE Translational Task Force of the International League Against Epilepsy. The aim is to provide acceptable standards and interpretation of results of electrophysiological depth recordings in vivo in control rodents.